Agaricales Production: A Systematic Review on its Representative Species’ Cultivation Process and Substrate Influence - Almodovar, Riana D. (Animo Repository, 2021)
Mushroom cultivation has long been of economic importance, specifically in Asian nations where most mushrooms are grown and sold. The globally popular Pleurotus ostreatus and a mushroom with similar composition profiles to it, Calocybe indica, are gaining recognition among farmers in urban areas due to their low-cost production and ability to grow on diversified substrates. Assessing the cultivation of both C. indica and P. ostreatus with selected substrates has been unexplored by researchers, most especially systematic reviews that focus on the cultivation of mushrooms in the Philippines. This paper sought to find the effectiveness of wheat straw, paddy straw, and sugarcane bagasse substrates in increasing specific growth parameters of C. indica and P. ostreatus. A systematic review with a narrative synthesis approach was performed to determine the effects of the chosen substrates on growth and yield parameters. The study utilized the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) as a basis for reporting the results and the Cochrane risk-of-bias tool to appraise the studies included in the review critically. Results show that wheat straw had increased the rate of spawn run and pinhead formation of both mushrooms, while paddy straw obtained high yield parameters. Though there was a lack of substantiation of a leading substrate among the three, paddy and wheat straw are substrates that might have the potential in increasing the mushroom’s yield and quality in the Philippines